NOTES ON SACRED SITES WORSHIPING IN KRASNODAR KRAI IN 1940-1960s: PILGRIMAGE AND ETHNICITY - Tuhtaev, Andrej Efimovic (History, Archeology and Ethnography of the Caucasus, 2021)
The paper presents an analysis of documents describing the history of holy sites worshipping in Krasnodar Krai in the Soviet era. The research aims to shed light on the little-known episodes of the history of pilgrimages in Soviet times North-West Caucasus from the perspective of relationships between Soviet authorities and ethnic minorities. Sources chosen for this work are archive documents of the Council for the Affairs of the Russian Orthodox Church. The pilgrimage had been prohibited by Soviet authorities, and the Orthodox clergy avoided supporting such practices as well. However, worshipping sacred sites was significant for folk religion all across the country. “Holy Hand” is an example of a place a visit to which was and remains an act of solidarization of Pontic Greeks communities in Krasnodar krai. This case demonstrates that the reason of why people kept maintaining pilgrims’ practices is the lack of other ways to support ethnicity. Pontic Greeks had certain support and political promotion in early Soviet nation-building project but was repressed afterward. As a result, pilgrimage turned out to be one of a few public dimensions of ethnic tradition. Representatives of the Council for the Affairs of Russian Orthodox Church visited Holy Hands many times and tried not only prevent pilgrimage but understand social background of such activities for more effective struggle against religion. Bureaucrats realized that pilgrimage is not only religious practice but also a place for keeping folk traditions alive. Folk traditions were positive phenomena for the social imagination of that time, and they weren’t necessary associated with religion. However, this didn’t help much in Council fight against pilgrimage, Soviet authorities could stop holy springs worshipping only through enforcement.